A carbazole-based "turn-on" two-photon fluorescent probe for biological Cu2+ detection vis Cu2+-promoted hydrolysis. (February 2016) - Li, Daoxue; Sun, Xin; Huang, Jianmin; Wang, Qi; Feng, Yan; Chen, Man; Meng, Xiangming; Zhu, Manzhou; Wang, Xin
Abstract: A carbazole-based "turn-on" two-photon fluorescent probe (CuCM ) was successfully designed and characterized, which can be used for Cu 2+ detection with high selectivity, low detection limit (32.8 nM), good water solubility, large Stokes shift (117 nm) and two-photon absorption cross sections (1328 GM at 860 nm). The fluorescence enhancement was attributed to the Cu 2+ -promoted C=N bond hydrolysis sensing mechanism, which is fully confirmed by the UV–vis absorption, fluorescence, 1 H NMR titration and MALDI-TOF mass analysis. Bio-imaging study revealed that the new probeCuCM could be used as an effective two-photon fluorescent probe for detecting Cu 2+ in living cells. Graphical abstract: A carbazole-based "turn-on" two-photon fluorescent probe (CuCM ) was developed for highly selective detection of Cu 2+ and bio-imaging under two-photon excitation. Highlights: CuCM showed a 66-fold fluorescence enhancement response to Cu 2+ in aqueous solution. The Cu 2+ -promoted C=N bond hydrolysis sensing mechanism was fully confirmed. CuCM can be used to detect Cu 2+ in living cells under two-photon excitation.